2021
DOI: 10.1177/2333794x21989555
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Standards For Infants and Young Children can be Implemented by Family Child Care Home Providers

Abstract: The study evaluated an educational intervention with family child care home (FCCH) providers to implement nutrition standards. A convenience sample of licensed California FCCH providers (n = 30) attended a 2-hour, in-person group training in English or Spanish on nutrition standards for infants and children aged 1 to 5 years. Provider surveys and researcher observations during meals/snacks were conducted pre- and 3 months post-intervention. Providers rated the training as excellent (average score of 4.9 on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…To address the training needs of FCCH providers, a multi-disciplinary, bilingual team of nutrition and health experts developed an in-person workshop in English and Spanish to share best practices on what and how to feed young children (Ritchie et al 2020(Ritchie et al , 2021. Given that one in 10 FCCH providers in California prefer to speak only Spanish and about one-quarter prefer Spanish in addition to English, a Spanish-language training was essential (Whitebook et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the training needs of FCCH providers, a multi-disciplinary, bilingual team of nutrition and health experts developed an in-person workshop in English and Spanish to share best practices on what and how to feed young children (Ritchie et al 2020(Ritchie et al , 2021. Given that one in 10 FCCH providers in California prefer to speak only Spanish and about one-quarter prefer Spanish in addition to English, a Spanish-language training was essential (Whitebook et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Given that one in 10 FCCH providers in California prefer to speak only Spanish and about one-quarter prefer Spanish in addition to English, a Spanish-language training was essential (Whitebook et al 2006). The team conducted a three-month pilot study of the workshop and found that, although the FCCH providers adopted many of the recommended feeding practices (Box 1), attending the workshop was challenging due to providers' busy schedules and transportation needs (Ritchie et al 2020(Ritchie et al , 2021. To improve accessibility and sustainability, the workshop content was converted to an interactive, online training with a digital teacher avatar named "Laura," which included videos, games and quizzes.…”
Section: Introductionmentioning
confidence: 99%